Exploring the dynamics of exercise intensity on male fertility and reproductive health: advancements and implications for fertility research - Abedpoor, Navid; Taghian, Farzaneh; Hajibabaie, Fatemeh (Frontiers in Reproductive Health, 2024)
On a global scale, 15% of couples experience infertility. Approximately 50% of these cases refer to male infertility. This literature review investigated the effects of exercise activities on male fertility and reproductive health. This subject was explored using studies conducted on human and animal models. Physical activity is widely recognized to improve overall well-being, but engaging in excessive exercise might potentially lead to male infertility due to the negative impact on hypothalamic-pituitary-testicular (HPT) function, increased oxidative stress, and the presence of chronic inflammation. Infertility might result from the fundamental factors that induce a decline in testosterone production and semen quality. Physical activity has the potential strategy to enhance male fertility in cases of infertility caused by obesity and diabetes. Exercise enhances spermatogenesis and semen quality in lifestyle-induced infertility by increasing testicular antioxidant defense, reducing pro-inflammatory cytokines, and promoting steroidogenesis.